Special educational needs, social care and health. Issue 1 (22nd January 2020) - Jay, Matthew A; Gilbert, Ruth
Abstract : Better understanding of the proportion of children who ever receive special educational needs (SEN) provision or social care services during school years is highly relevant for healthcare as reductions in one or more of these services could impact on healthcare. Using the National Pupil Database linked to the all-of-England children looked after return and children in need census, we estimated the cumulative incidence of SEN status among (1) children ever in care during school, (2) children in need but not care, and (3) neither. We observed a very high proportion of children who were in care or need during school years had SEN provision at some point (83% and 65%, respectively), and that a high proportion of children in neither of these groups did so, too (37%). Healthcare, SEN provision and social care services focus on a similar population of children. Better integration of these services could lead to synergies and cost-efficiencies and better support for these children and their families.